Maintenance and Reliability Improvement of Roller Bearings Operating at High Temperature: Thermal Stress Analysis Approach (International Journal of Innovative Research in Engineering & Management, 2024)
In this paper the authors present the  outcome of an experimental maintenance and reliability  investigation conducted to prevent operation failure of  pinion bearings caused by excessive temperature with a  case study of a 1360kW ball mill driveline system in  mineral processing application. Aiming to improve the  overall plant performance, the lubrication regime of pinion  bearings as key component within the ball mill driveline  system was studied to determine possible causes of  temperature increase at 80 to over 100C with a 25 - 30C  gap over the maximum operating temperature. An analytical  review of maintenance data is conducted to mitigate future  operational risks by implementing a new lubrication regime  and shutdown frequency for overall statutory inspection.  Accelerated life test based inverse power law has been  applied to identify the root causes of excessive bearings  temperature to establish immediate short-term solution  paths towards a guaranteed less required maintenance asset  improvement practice, less operational cost, and plant  availability enhancement. Furthermore, long-term solutions  have been proposed based on modelling by thermal network  approach of pinion bearings for thermomechanical stress  prevention. A single parameter based accelerated test on  pinion bearings was applied to establish operational fault  tolerant factors to be considered for asset capability  improvement, which remains an open question for future  studies. These actions have shown significant improvement  with temperature decrease between 15 and 25C below the  maximum required temperature.
Keywords: Pinion Bearing; Lubrication Regime; Maintenance Data; Thermal Modelling; Reliability Improvement